Understanding Commuter’s Motivation of Transportation Choice: A Case Study of Greater Jakarta - Theodorus Pandhu Bhaskoro Pradonoputro; Otsuka Kozo (Institut Transportasi dan Logistik Trisakti, 2021)
Among the various modes of transportation, road transport is one of the most common modes of transport due to the comfortability and ease of commute. It is no wonder that road transport has become the primary energy consumption, which also significantly contributes dangerous levels to the ever-increasing pollution. Jakarta as the capital city of Indonesia is undeniably the most massive contributor to pollution in the world, and its complex transportation problems led to the city ranks highest in CO2 emission. One of the leading causes of transportation problems in Jakarta is the low percentage utilization of public transport. Therefore, the primary purpose of this study is to explore the reasons behind the people's decision in selecting travel options, especially the adoption of green commuting behavior like public transportation; the analysis of which was explicitly taken from daily commuting using probit regression. The estimation results reveal that in Greater Jakarta, both educational attainment and population density have a negative correlation with the people’s decision to utilize mass transportation since the unreliability of the transportation system lessens the benefit of using public transport in comparison with that of private transport.